Juvenile fibromyalgia in an adolescent patient with sickle cell disease presenting with chronic pain. (1st October 2015) - Ramprakash, Stalin; Fishman, Daniel
Abstract : Juvenile fibromyalgia in children with sickle cell disease has not been reported in the literature. We report an adolescent patient with sickle cell whose pain symptoms progressed from having recurrent acute sickle cell pain crisis episodes to a chronic pain syndrome over several years. He was eventually diagnosed with juvenile fibromyalgia based on the clinical history and myofascial tender points and his pain symptoms responded better to multidisciplinary strategies for chronic fibromyalgia pain. Chronic pain in sickle cell disease is an area of poor research, and in addition there is inconsistency in the definition of chronic pain in sickle cell disease. Central sensitisation to pain is shown to occur after recurrent painful stimuli in a genetically vulnerable individual. In a chronic pain condition such as fibromyalgia central sensitisation is thought to play a key role. Fibromyalgia should be considered as one of the main differential diagnosis in any sickle cell patient with chronic pain.